THE EFFECT OF PRICING AND MARKETING COMMUNICATION ON CONSUMER SATISFACTION PT. SOURCE OF FORTUNE - Vanessa Vicario; Yusuf Taufik; Rudyanto Simanjuntak (Journal of Financial Management & Accounting, 2024)
Pricing is the most important decision and calculates costs directly related to the product or service being marketed. Marketing communications is an effort to make all marketing and promotional activities of the company produce a unified and consistent image for consumers. Consumer satisfaction is the level of consumer's feelings after comparing what the consumer has received with the expectations he desires. This research uses quantitative descriptive research. The data analysis technique that will be used in this research is multiple linear regression analysis. The measurement scale used is the Likert scale. Simultaneously there is a significant influence between pricing variables and marketing communications on consumer satisfaction at PT. Source of Fortune. Meanwhile, it was partially found that the pricing variable had a significant effect on consumer satisfaction at PT. Source of Fortune. Partially, it was found that marketing communication variables had a significant effect on consumer satisfaction at PT. Source of Fortune. Keywords: Pricing, Marketing Communication, Satisfaction